Innovation in Trás-os-Montes traditional products: consumer perception on extra long maturation sheep cheese - Mendonça, Álvaro (2018)
Cheese is an important food for a healthy diet. Portugal is a country with a huge tradition in the manufacture of cheese from the use of small ruminants. Herds managed in production systems based on pastoralism, with cycles of production according to animal physiology, shaped by the time and the expertise of the shepherd. The production of traditional cheeses is a very strong habit in rural communities and the study of consumer acceptance of aged cheese is an important factor for the valorisation/competitiveness strategy. This work is based on data from a survey on the consumption preferences of Extra Long Maturation (ELM) sheep's cheese. The objective of the study was to identify the consumer profile, cheese consumption habits and to compare consumers' perception about the characteristics of cheeses with different maturation periods (6, 11 and 12 months). For this, a study was developed based on a sample of 107 consumers who went to a supermarket in Bragança on May 29, 2015 and the National Agricultural Fair 2015, in Santarém on June 11. To collect the data, a questionnaire was used with questions about socioeconomic characteristics of the consumer, frequency of general cheese consumption and the sensorial perceptions of consumers about appearance, aroma and taste, in a scale 1 to 9; and, hardness and perceived fat and salt content, in a scale 1 to 5. Data analysis was done using SPSS 23.0 and involved the use of descriptive statistics to identify the consumers’ profile and cheese consumption habits; and, the Friedman test to verify if there were statistically significant differences between cheeses with different maturation periods. The three cheeses were presented to consumers in a plastic dessert plate with the cheese code inscribed on the plate next to the slice of cheese with 6, 11 and 12 months. Each slice was about 4 millimeters thick. There was also a plate with three toasts, a napkin and a glass of water. Consumers were informed that they should clean the palate between tasting each of the three cheese slices since the slices were supplied at the same time. To cleanse the palate, consumers could turn to water and/or toasts. The majority of the participants (76.6%) consumed cheese more than once a week (Figure 1), were male (57.9%), aged between 25 and 64 years old (77.6%), married or in a stable relationship (48.1%), lived in households with 3 or 4 people (52.5%) with a net monthly household income between € 1,001 and € 3,000 (44.9%) and had a higher education degree (63.6%) (Table 1).